Total Phenolics, Total Carotenoids and Antioxidant Activity of Selected Unconventional Vegetables Growing in Bangladesh - Alam, Mohammad K.; Rana, Ziaul H.; Kabir, Nazura; Begum, Parveen; Kawsar, Mahbuba; Khatun, Maksuda; Ahsan, Monira; Islam, Sheikh N. (Current Nutrition & Food Science, 2020)
Background: Phenolics and carotenoids are natural antioxidants, which provide health benefits and protect against degenerative chronic diseases. Utilization and identification of foods with a high content of these have received greater attention nowadays. Objective: The present study reports the total phenolics (TPC) and total carotenoids (TCC) contents of thirty-two selected unconventional vegetables growing in Bangladesh. In addition, they were also analyzed for their antioxidant potentials. Methods: Folin-Ciocalteu and acetone-petroleum ether extraction followed by spectrophotometric measurements was employed for TPC and TCC, respectively. The antioxidant capacities of the selected unconventional leafy vegetables were analyzed using DPPH and Trolox equivalent antioxidant capacity (TEAC) assays. Results: The results revealed that the TPC ranged from 82.41 mg GAE/100 g in Kiokro to 2711.05 mg GAE/100 g in Mrolapiong whereas the TCC values ranged from 43.05 μg/100 g in Fala to 12863.54 μg/100 g in Roktodrone. The study findings also revealed that the selected plant samples exhibited high antioxidant capacities. Mrolapiong demonstrated the highest DPPH inhibition (91.31%) and TEAC (485.55 μmol Trolox/g) value than others. The antioxidant capacities were attributed to phenolic compounds as there exists a positive correlation between these two variables. Bioactive phytochemicals are widely distributed in these vegetables, although their amounts vary among the different types of vegetables. Conclusion: The study results suggest that the analyzed vegetables may provide a possible source of dietary antioxidants and serve as materials for functional foods. Therefore, their production and consumption must be encouraged in order to preserve biodiversity and prevent their extinction.
Keywords: total phenolic content